КЛАССИФИКАЦИЯ И ТЕНДЕНЦИИ РАЗВИТИЯ МЕЖДУНАРОДНЫХ ДОКУМЕНТОВ В СФЕРЕ ОБЕСПЕЧЕНИЯ И ЗАЩИТЫ ПРАВ ЖЕНЩИН - Фируза Хамдамова (World Science, 2019)
The article is devoted to the classification of international documents in the field of ensuring and protecting the rights of women. The author systematizes them for several reasons, namely: depending on the subject who accepted the document, according to its legal nature, on the range of issues regulated by the document, its geographical scope. The author also raises the question of the reasons for the ineffectiveness of some documents on women’s rights, in particular, the issue of reservations and cultural relativism. Thus, today there is a huge array of international documents on the rights of women, which are a fairly solid legal basis for effectively ensuring the rights of women. These documents are adopted in various forms - in the form of declarations, recommendations, conventions and programs or strategies of actions, that is, in the form of documents of a mandatory or recommendatory nature. An analysis of their content made it possible to highlight the most priority areas of international legal cooperation in the field of ensuring the rights of women, namely, maternity protection, ensuring equality in the family and the world of work, and protecting women from violence. More and more documents are being adopted in order to protect vulnerable layers of women facing multiple discrimination. The adoption of documents on the protection of the most vulnerable categories of women, that is, women exposed to multiple discrimination, is one of the trends in the development of international legal standards on women’s rights.